Fluid resuscitation strategy in patients with placenta previa accreta: a retrospective study - Zhou, Fan; Liu, Na; Huang, Guiqiong; Yu, Haiyan; Wang, Xiaodong (Frontiers in Medicine, 2024)
Objectives: Obstetric hemorrhage is the leading cause of maternal death worldwide. Placenta previa accreta is one of the major direct causes of postpartum hemorrhage, accounting for two-thirds of obstetric hemorrhage cases. Fluid resuscitation is a life-saving procedure for patients suffering from massive hemorrhage. This study aims at evaluating the risk factors of massive hemorrhage and appropriate fluid resuscitation strategy in patients with placenta previa accreta.Methods: This study retrospectively analyzed the risk factors for massive hemorrhage, clinical characteristics, and perinatal outcomes of patients with placenta previa accreta. Maternal noninvasively evaluated hemodynamic indicators, including maternal heart rate, systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and shock index, were collected and analyzed at nine time points, from the administration of anesthesia until the end of procedures, in patients diagnosed with placenta previa accreta and receiving different fluid supply volumes.Results: Complicated with placenta increta/percreta and gestational age of delivery later than 37 weeks are two independent risk factors of massive hemorrhage in patients with placenta previa accreta. A total of 62.27% (170/273) patients diagnosed with placenta increta/percreta had massive hemorrhage, significantly higher than those diagnosed with placenta previa accreta (5.88%, 6/102).Patients delivered after 37 weeks of gestation had significantly higher ratios (86.84%, 99/114) of massive hemorrhage compared with those delivered between 36 and 36 +6 weeks of gestation (36.39%, 63/178). Maternal SBP, DBP, and MAP started to decrease immediately after the baby was delivered and reached a relatively stable trough state at 15 30 minutes after delivery. No statistical differences were found in hemodynamic indicators, the occurrence of hypotension, or in-hospital days after the procedure among the transfusion volumes <30 ml/kg, 30 80 ml/kg, and ³80 ml/kg groups.Conclusions: Patients with a suspected diagnosis of placenta previa accreta should plan to deliver before 37 weeks of gestation. The ability to identify concurrent placenta increta/percreta should be improved to schedule a reasonably rapid perioperative plan. Restrictive fluid resuscitation could achieve good effects in maintaining hemodynamic stability in patients with placenta previa accreta.A time period of 15-30 minutes after delivery is the critical stage for fluid resuscitation.